Development of Interactive Powerpoint Media to Stimulus the Ability to Recognize Flat Shape in Children Aged 5-6 Years - Della, Ellyta Iman; Ismail, Moh Hemli; Asriadi AM, Muh (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
This research aims to develop a product to increase children's interest in learning and enrich the variety of learning media. The method used in this research is Design and Development (D&D) and in creating or developing products, researchers use the ADDIE model. The validation test results for interactive PowerPoint media from material experts showed a score of 3.6 in the